A comparison of product dependence among cigarette only, ENDS only, and dual users: Findings from Wave 3 (2015–2016) of the PATH study. (1st December 2020) - Kaplan, Bekir; Alrumaih, Fahd; Breland, Alison; Eissenberg, Thomas; Cohen, Joanna E.
Highlights: Few nationally representative studies have assessed tobacco dependence among dual users. Cigarette and ENDS dependence among dual users were examined. There was no difference in cigarette dependence between dual and cigarette only users. Dual users' ENDS dependence was lower than that for ENDS only users. ENDS appeared to produce less dependence than cigarettes among dual users. Abstract: Introduction: Little is known about differences in tobacco product dependence among people who use two tobacco products versus one. Self-reported product dependence among individuals using cigarettes only, electronic nicotine delivery systems (ENDS) only, and both cigarettes and ENDS (dual users) was compared. Method: PATH Wave 3 data were collected between 2015 and 2016. We used 11 Wisconsin Inventory of Smoking Dependence Motives items to assess cigarette and ENDS dependence, averaged to generate Cigarette Dependence (CD) and ENDS Dependence (ED) scores. Linear regression models were used to assess the association between tobacco use groups and the two dependence scores. Results: Our analytic sample included 5538 (91.5 %) cigarette only, 399 (6.7 %) ENDS only, and 108 (1.8 %) dual users. There was no difference in CD between cigarette only and dual users. ENDS only users' ED (2.11, SE = 0.05) was higher than dual users' ED (1.67, SE = 0.04) (p < 0.05). Dual users' mean ED (1.70, SE = 0.09) was significantly lower than their CD (3.03, SE = 0.11) (p < 0.001), and ENDS only users' ED (2.34, SE = 0.05) was significantly lower than cigarette only users' CD (2.94, SE = 0.02) (p < 0.001). Conclusion: While there was no difference in CD between dual and cigarette only users, dual users' ED was lower than that for ENDS only users. ENDS appeared to produce less dependence than cigarettes among dual users. Given the high nicotine concentration ENDS products that entered the market after PATH Wave 3 data were collected, future research should examine ED among ENDS only and dual users.